Hass avocado producing farms, consolidated family farming model in Fusagasugá (Colombia). - Cárdenas Cárdenas, María Alejandra; Sánchez Rojas, Edwin Fernando; Vasquez Hortua, Edgar (Uptc, 2023)
Consolidated family farming has agricultural resources and allows the generation of surpluses and is integrated into the production chains. The objective of the research was to characterize this model of family farming in the municipality of Fusagasugá with the production of Hass avocado, based on the identification of social, economic factors and agricultural management practices. It was carried out during August and September of the year 2022, a sample of 52 farmers was selected for convenience and it was found that in the production unit social relations converge, contributions for gender equality, participation in community action boards, force of family work , clarity in land tenure, access to credit, presence of different crops that contribute to security and food sovereignty on farms, use of composting, vermicompost and organic pesticides as supplements for the cultivation of Hass avocado that help to the conservation of the ecosystem.